The Interest Level Analysis of Online Transportation in Tiban Area, Batam - Grace Febiola Parura; Yusra Aulia Sari (Fakultas Teknik Sipil dan Perencanaan, 2023)
This study's population, which consists of customers who use online transportation services, tries to ascertain how people in Tiban feel about utilizing it. The questionnaire approach was utilized in the sampling procedure, and as many informants as feasible from various ages and professional backgrounds were given connections. The analysis is a descriptive qualitative method suitable for giving information and facts. The findings of the questionnaire revealed that using online transportation benefits the neighborhood. People may travel easily using online transportation, providing several promotions, and ensuring client safety. The study's findings demonstrate how consumers see internet transportation as a significant and favorable outcome. Public perceptions may affect how people regard online transportation. Because online transportation serves the community, its capabilities and other characteristics can influence its opinions. The quality of the service itself determines whether Internet transportation is seen favorably or unfavorably by society. The performance of online transportation drivers while delivering services to the community supports service success in the service sector. Both negative and positive customer opinions of online transportation will be influenced mainly by the services offered to the community. As the preceding explanation demonstrated, the community, particularly the citizens of Tiban, is impacted by the usage of online transportation based.